Improve your Reading Comprehension Using POP Up Book Media in 2nd Grade of Deaf Children at Plus Marhamah Elementary School:Single Subject Research) - Afrila Afrila; Damri Damri (Edumaspul: Jurnal Pendidikan, 2023)
This research own the aim of improving reading comprehension skills using pop - up books for deaf children . Researcher do observation and with the result that a deaf child in grade 2 elementary school is difficult in reading comprehension . Child to be subject in researcher t ian This only can answer 1 of 10 questions given . _ This problem is due to the difficulty of children communicating due to their limitations and also the lack of media used when learning at school . The use of this pop - up book can help children to understand the meaning of reading because of the raised pictures on the book . In this study using the single subject research (SSR) method with ABA design . Child have an average level condition A1 ie 1 9 , the average level condition B is 75.5 , the average level condition A2 is 90 . From the results analysis of the data showing that Children's reading comprehension ability increases when using pop - up book media.